Einblicke in den Streit zwischen Leib und Kopf – Eine Neuedition und Textanalyse von tTurin CGT 58004 (Cat. 6238) - Biase-Dyson, Camilla di (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
This study of the Late Egyptian literary work, The Contendings between the Body and the Head , presents a new edition of the Turin writing tablet CGT 58004. Having visualised recent photos of the tablet with DStretch, a new transcription of the text can be presented, along with a new translation. A textual analysis, moreover, reveals the highly playful and metaphorical nature of the language, whereby the feminine body paints a vivid picture of her roles and responsibilities in order to challenge the primacy of the masculine head.